2023
DOI: 10.1007/s10865-022-00385-4
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and impact of a remote moderate-intensity yoga intervention on stress and executive functioning in working adults: a randomized controlled trial

Abstract: The feasibility of a moderate-intensity yoga intervention, delivered remotely via supervised and unsupervised sessions, and its psychosocial and cognitive effects have not been thoroughly investigated. This randomized controlled trial assessed feasibility and preliminary efficacy of an 8-week moderate-intensity yoga intervention (3×/week, 50 min) delivered remotely (vs. a waitlist control arm), on stress and cognitive functioning. Participants (n = 86) were low active, full-time working adults (81.40% female; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The impact of vinyasa yoga practice on reducing stress and reducing problems with falling asleep has already been shown in a study on a group of oncologists who declared an improvement in well-being after 3 months of practice ( 37 ). Notably, in clusters 4 and 5 ( Figure 3 ), the respondents to whom the desire to reduce stress through yoga practice was assigned were predominantly those with a short history of the practice allowing us to assume, as confirmed by the results of other researchers, that yoga has a positive effect on stress management role ( 67 , 75 , 76 ). Respondents who have been practicing for years are less likely to report a need for stress reduction ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The impact of vinyasa yoga practice on reducing stress and reducing problems with falling asleep has already been shown in a study on a group of oncologists who declared an improvement in well-being after 3 months of practice ( 37 ). Notably, in clusters 4 and 5 ( Figure 3 ), the respondents to whom the desire to reduce stress through yoga practice was assigned were predominantly those with a short history of the practice allowing us to assume, as confirmed by the results of other researchers, that yoga has a positive effect on stress management role ( 67 , 75 , 76 ). Respondents who have been practicing for years are less likely to report a need for stress reduction ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 52%
“…Significantly few people indicated that spiritual motivation is the main reason for exercise (Figure 4). Vinyasa yoga is a dynamic style characterized by the diversity that allows practitioners to choose the intensity of the practice according to their needs and abilities (37,73,74). The impact of vinyasa yoga practice on reducing stress and reducing problems with falling asleep has already been shown in a study on a group of oncologists who declared an improvement in well-being after 3 months of practice (37).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Zope et al [48] concluded, "In the context of the pandemic COVID -19, yoga may improve mental health status, immunity to viral infections, systemic health parameters, quality of life, and/or survival in patients with comorbidities." Another paper published by Phansikar et al [49] showed that it is feasible to implement a moderate-intensity yoga intervention with synchronous and asynchronous technology at home for working adults with stress symptoms without compromising contact safety during the pandemic.…”
Section: Journal Of Yoga and Physiotherapymentioning
confidence: 99%